Green-based supplier selection using BWM and VIKOR methods in the Indonesian manufacturing sector - Alkolid, Yudam; Kurniawan, V. Reza Bayu; Ma'arif, Syamsul; Zaibidi, Nerda Zura; Othman, Norfaridatul Akmaliah (Faculty of Engineering, Universitas Negeri Yogyakarta, 2023)
The selection of green-based suppliers remains a challenge for manufacturing firms in Indonesia. In today's business landscape, it is crucial to consider green aspects as part of sustainability practices when choosing suppliers. However, there is a limited number of studies providing frameworks for selecting suppliers based on green factors, particularly in developing countries. This study aimed to propose a framework for selecting suppliers using multicriteria decision-making (MCDM) techniques. A case study was conducted in an Indonesian metal manufacturing company that considers carbon reduction and incorporates traditional supplier selection factors such as quality, cost, and capacity. The study integrated two MCDM techniques, namely the best-worst method (BWM) and ViÅ¡ekriterijumsko Kompromisno Rangiranje (VIKOR), to evaluate and select green-based suppliers. BWM was employed to determine the weights of the criteria, while VIKOR ranked the suppliers. Seven criteria were identified, including cost (C1), quality (C2), delivery time (C3), technology application (C4), compliance with environmental regulations (C5), green practice certification (C6), and green efforts (C7). Nine suppliers were screened and ranked accordingly. The results indicate that quality, delivery time, and cost are the top three ranked criteria based on their importance. Further, this study includes nine suppliers in which supplier S7 demonstrates the best performance compared to the others. This study highlights that in Indonesia, most organizations tend to prioritize traditional criteria, while green factors are still overlooked. However, the company examined in this study has taken the initiative to include environmental factors in its decision-making process. The findings of this study contribute to the development of a framework for selecting green suppliers in a developing country context.